1974
DOI: 10.1029/jb079i020p03009
|View full text |Cite
|
Sign up to set email alerts
|

Inherent vector discrepancies in geomagnetic main field models based on scalarF

Abstract: We have investigated the spherical harmonic analysis (SHA) of scalar intensity F. The method used was the analysis of simulated data, derived by adding pseudorandom noise to surface values (with equiangular spacing) synthesized from existing spherical harmonic coefficients (SHC). An advantage of using simulated data is that this makes possible the computation of vector as well as scalar residuals. In general, similar results were obtained regardless of whether the number of input SHC used in the synthesis of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…It has already been shown that the Backus effect can be significantly reduced when a few vector data from ground-based observatories are included in the field model derivation (Hurwitz and Knapp, 1974;Stern and Bredekamp, 1975). This effect is more pronounced when these observatories are located near the equator (Barraclough and Nevitt, 1976;Lowes and Martin;1987).…”
Section: Reduction Of the Backus Effect Using Observatory Datamentioning
confidence: 99%
“…It has already been shown that the Backus effect can be significantly reduced when a few vector data from ground-based observatories are included in the field model derivation (Hurwitz and Knapp, 1974;Stern and Bredekamp, 1975). This effect is more pronounced when these observatories are located near the equator (Barraclough and Nevitt, 1976;Lowes and Martin;1987).…”
Section: Reduction Of the Backus Effect Using Observatory Datamentioning
confidence: 99%
“…Considerable effort has been devoted to finding a method by which satellite intensity data could be used to produce high-quality field models. It was found that including vector component data from magnetic observatories, especially close to the equator, would significantly reduce the effect of the non-uniqueness (Hurwitz and Knapp, 1974;Barraclough and Nevitt, 1976;Gubbins and Bloxham, 1985;Lowes and Martin, 1987;Ultré-Guérard and Achache, 1997). This observation was explained by Khokhlov et al (1997), who demonstrated that, in principal, the Backus effect could be eliminated with knowledge of the position of the geomagnetic dip equator, the points on the Earth's surface at which the vertical component of the field is zero.…”
Section: Introductionmentioning
confidence: 84%
“…This occurs mostly in the equatorial region, and it results in large differences in the vertical component. This effect was discovered and described when no spacecraft vector magnetic field measurements were available (e.g., Backus 1970;Hurwitz and Knapp 1974;Lowes 1975;Stern and Bredekamp 1975). Different strategies have been proposed to alleviate it.…”
Section: Model Parametrization and Statisticsmentioning
confidence: 95%
“…Different strategies have been proposed to alleviate it. Hurwitz and Knapp (1974) were probably the first to include vector data in the equatorial region, to better constrain the position of the magnetic equator and resolve the sectoral harmonics. These additional data can be provided by the magnetic observatories, which have however a poor geographic distribution.…”
Section: Model Parametrization and Statisticsmentioning
confidence: 99%